Effect of Midwifery Students' Negative Clinical Experiences on Their Emotional Labor Behaviors - BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objectives: Emotional labor is the effort type that organizations expect from their employees or the effort that the individual makes based on his/her mood. Negative clinical experiences in the workplace may have long-term influence on emotional labor behavior. Aim of this study was carried out to determine the effect of midwifery students' negative experiences in clinical practices on their emotional labor behaviors. Methods: The study is a mixed-methods study. Thematic analysis and descriptive was used. The study was conducted from November to December 2018 with 370 midwifery students in Istanbul. The relevant data were collected via a Descriptive Information Form and Emotional Labor Behavior Scale of Nurses (ELBS). Results: The mean age of the students recruited for the research is 21.57 +/- 1.51. Eighty-five percent of students (n=314) were identified to have at least one negative clinical experience, which decreased their motivations to be a midwife. Healthcare professional's behaviors towards pregnant women during childbirth rank first (48.1%) among these negative experiences. A little more than the half of the students (51%) react to these negative experiences by staying away from the setting. It was identified that ELBS total score mean of students were 96.52 +/- 11.92 and also that as students' fear to vaginal birth management increased, their ELBS scores decreased (p=0,00, r=-0,22). It is determined that clinical negative experiences do not affect students' emotional labor behavior (p>0,05). Conclusion: The factor affecting a large part of students' motivation to be midwife negatively is the healthcare professional's negative behaviors towards pregnant women and students. Within this context, it must be attempted to make healthcare personnel behave in a more humanistic and professional way towards women and students. Therefore, midwifery education programs should be planned and written about the qualifications that students should be knowledgeable and equipped to understand the emotional needs of women.
Keywords: Student midwives; clinical negative experience; emotional labor behavior; MIDWIVES EXPERIENCES; POSTTRAUMATIC-STRESS; MIXED-METHODS; EVENTS; CHILDBIRTH; EXPOSURE; WORK; CARE